RELEVANSI STANDAR AKUNTANSI UNTUK ENTITAS MIKRO, KECIL DAN MENENGAH DI INDONESIA: KEBUTUHAN ATAS KEBERLANGSUNGAN ENTITAS MIKRO, KECIL DAN MENENGAH DI INDONESIA DI TENGAH KRISIS EKONOMI - Ruswan Nurmadi (METHOSIKA: Jurnal Akuntansi dan Keuangan Methodist, 2020)
Financial Accounting Standards for Micro, Small and Medium Entities (SAK - EMKM) in Indonesia are absolutely necessary. With SAK - EMKM, MSME actors can compile a financial report that can describe the actual situation of the business situation carried out by MSME players. By having a financial reporting, MSME actors can see whether their business is sufficient with their own capital or must be supplemented with outside capital, such as loans from banks. Therefore, having a standardized financial reporting is a must because it is a requirement for banks to obtain business loans. This research is a literature study to see the relevance of Accounting Standards for Micro, Small and Medium Entities in Indonesia for the sustainability of Micro, Small and Medium Entities in Indonesia amid the Economic Crisis.